BASIC PRINCIPLES OF TREATMENT OF ANEMIA AND THROMBOPHILIC STATUS VIN PREGNANT AND POSTPARTUM WOMEN - E. S. Egorova (Акушерство, гинекология и репродукция)
The article gives an overview of the forms of anemia, the impact of anemia in pregnancy and obstetric complications. Overwieved the main approaches to the treatment of anemia during pregnancy. A comparative analysis of the use of drugs of ferrous and ferric iron. Discussion of the possibilities given relief thrombophilic conditions in combination with anemia. Formulated the main principles of survey of pregnant women with anemia, as well as the treatment of anemia in pregnant and postpartum women.